2015
DOI: 10.1016/j.isprsjprs.2015.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Mapping paddy rice planting areas through time series analysis of MODIS land surface temperature and vegetation index data

Abstract: Knowledge of the area and spatial distribution of paddy rice is important for assessment of food security, management of water resources, and estimation of greenhouse gas (methane) emissions. Paddy rice agriculture has expanded rapidly in northeastern China in the last decade, but there are no updated maps of paddy rice fields in the region. Existing algorithms for identifying paddy rice fields are based on the unique physical features of paddy rice during the flooding and transplanting phases and use vegetati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
111
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 220 publications
(135 citation statements)
references
References 50 publications
2
111
0
1
Order By: Relevance
“…Likewise, in America, the highest agreement occurs in Cuba (i.e., 7.81%), where rice constitutes 50% of agricultural production. Actually, rice production across these environments is characterized by an initial flooded phase and a typical phenology that can be readily identified from remote sensing data, resulting in good discrimination and classification [55]. Similar to previous studies [19], in Africa, the highest agreements are located in the transition zone between the Soudanien and Sahelian bands, running from west Senegal to east Ethiopia.…”
Section: Spatial Agreement and Discrepanciessupporting
confidence: 78%
“…Likewise, in America, the highest agreement occurs in Cuba (i.e., 7.81%), where rice constitutes 50% of agricultural production. Actually, rice production across these environments is characterized by an initial flooded phase and a typical phenology that can be readily identified from remote sensing data, resulting in good discrimination and classification [55]. Similar to previous studies [19], in Africa, the highest agreements are located in the transition zone between the Soudanien and Sahelian bands, running from west Senegal to east Ethiopia.…”
Section: Spatial Agreement and Discrepanciessupporting
confidence: 78%
“…To fulfill the food demand of large population, Asian countries often adopt intensive agriculture to increase grain production on limited cropland extents with heavy capital and labor inputs. Multiple cropping, a common practice of intensive agriculture that grows multiple crops in the same cropland during a single growing season, makes full use of the light-heat resources as well as other natural conditions to increase the agricultural production capacity [4][5][6]. Simultaneously, multiple cropping results in a series of subsequent environment and social issues, such as agricultural land use, water use and nutrient applications, cropland managements, and the reciprocal feedback of climate changes [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Others Gumma et al 2016;Zhang et al 2015;Zhou et al 2016) showed the ability of phenology-based algorithms in paddy rice mapping by using MODIS time-series and/or by integrating MODIS with other higher spatial resolution data such as Landsat 8 OLI images. This research further re-iterates the strength of MODIS time-series data in cropland and/or specific LULC mapping.…”
Section: Discussionmentioning
confidence: 99%